Adaptation of Sharia Law to Russian Criminal Law by Population of Western Turkestan and Siberian Bukharans in Late 18th — Early 20th Centuries - O. N. Naumenko; U. I. Abdullaev (Научный диалог)
This article examines the state policy of aligning Muslim law with Russian legislation in different cultural-historical contexts. It is demonstrated that the implementation of this mechanism was carried out among the Siberian Bukharans in the late 18th century, and from the second half of the 19th century, these methods were applied to Western Turkestan under the protectorate of the Russian Empire. Sources include documents from the Central State Archive of the Republic of Uzbekistan and the State Archive of the Tyumen Region in Tobolsk. The re-search methodology is based on the systems theory of K. L. von Bertalanffy, utilizing comparative-historical and comparative-legal research methods. The authors conclude that the dissonance between Russian legislation and Western Turkestan not only reflected differences between two distinct legal systems and religious-legal cultures but primarily highlighted the gap between medieval and contemporary legal concepts for that time. The adaptation of Western Turkestan to Russian legislation shaped unified legal concepts and paved the way for transforming the multi-confessional population of the Russian Empire into a unified civic entity. This laid the groundwork for the coexistence of Uzbekistan and Russia within the USSR and later facilitated the development of an independent Uzbekistan using legislation closely aligned with Russian and European legal systems.